A Statistical Analysis of Internet Based ICT adoption among SMEs in India: Drivers and Challenges - Kayalvizhi, S.; Gunasekar, T.; Thenmozhi, S. (IJRDO - Journal of Applied Management Science, 2016)
The purpose of this study is to explore the key drivers and challenges of Information and Communication Technologies (ICTs) adoption by Small and Medium Sized Enterprises (SMEs) in India. SMEs play a major role in developing and developed economies in job creation and diversification of economic activities. The literature shows that while there are many drivers of ICTs adoption by SMEs, there are equally many challenges from various factors. SMEs that effectively utilize ICTs can compete efficiently in both domestic and global arenas. Understanding the drivers, and challenges to ICT adoption by SMEs especially in the developing countries like India have not been addressed adequately. This study attempt to address this gap. A survey questionnaire was used to collect data from 250 different SMEs in India. Quantitative approaches were used for data analyses. The study identified the key challenges to ICT adoption as lack of internal capabilities, high cost of ICTs, poor infrastructure, financial constraints and lack of information about suitable ICT solutions and lack of time to implement. The study also identified the key drivers of ICT adoption as the desire to increase customer service and responsiveness, increase ability to compete, improve overall communication, increase sales and profit and to have better access to information. The result of the study will be beneficial to current and future SMEs in India.